Pengaruh Penggunaan Teknik Think Talk Write Terhadap Keterampilan Menulis Teks Berita Siswa Kelas VIII SMP N 17 Padang - Putri Ramadhani Ramadhani; Dina Ramadhanti; Ria Satini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This study aims to describe the effect of using the Think-Talk-Write technique on the news writing skills of grade VIII students of SMP Negeri 17 Padang. This type of research is quantitative research, the method uses the pre-experimental method with the one group pretest-posttest design. The population in this study were all eight graders of SMPN 17 Padang consisting of eight classes, namely VIII.a, VIII.b, VIII.c, VIII.d, VIII.e, VIII.f, VIII.g, VIII.h and the sample class in this study is class VIII.f. The X variable is the Think Talk Write technique, while the Y variable is the ability to write news texts. The research instrument used is the test. Data collection techniques by providing performance tests. The results of learning to write news texts for Grade VIII students of SMP Negeri 17 Padang before and after using the Think Talk Write technique are then interpreted based on arithmetic averages. The results of this study are that there is an effect of using news texts for class VIII students of SMP Negeri 17 Padang before using the Think Talk Write technique because tcount = 3.17 and ttable = 1.71 The criteria for testing t are accepted if tcount>ttable, in other words H1 is accepted and H0 rejected.